RISK MATURITY FOR SUSTAINABILITY ASSITANCE: A LONGITUDINAL STUDY IN CONSTRUCTION COMPANY - Basbeth, Firdaus (Journal of Sustainable Community Development (JSCD), 2024)
A risk maturity assessment is a useful tool for construction firms to evaluate both their strengths and weaknesses in risk management procedures and take the required steps to improve them. The assessment was conducted in a building construction project, to determine the level of risk maturity for two consecutive years in May, 20023 and 2024. The activities were carried out in four projects, covering the most important activities of risk management and analyzing the improvement. The RMM matrix used in this article is adapted from the Logic Manager, which consists of seven sections, each focusing on a different core ERM attribute. These seven areas are further broken down into 25 success components and 71 competency drivers that show exactly where an organization's ERM program stands on five maturity levels, ranging from Ad Hoc to Leadership. The model helps construction companies understand their current risk management performance. We tested the model by measuring the risk maturity level of an industrial partner working on civil infrastructure projects in Indonesia. The result of the Risk Maturity Level (RML) assessment is 3.6 (Managed), an increase of 0.3 points from the result in 2023 (3.3), reflected in several achievements in criteria 1, 2, 3, 4, 6 and 7, including a Risk committee formed to plan based on external and internal analysis of the organization. This study demonstrates that employing risk maturity management techniques may promote corporate development and efficiency, resulting in resilience and sustainability.